2018
DOI: 10.1097/01.ogx.0000534708.24689.e0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Versus Immediate Cord Clamping in Preterm Infants

Abstract: BACKGROUNDThe preferred timing of umbilical-cord clamping in preterm infants is unclear. METHODSWe randomly assigned fetuses from women who were expected to deliver before 30 weeks of gestation to either immediate clamping of the umbilical cord (≤10 seconds after delivery) or delayed clamping (≥60 seconds after delivery). The primary composite outcome was death or major morbidity (defined as severe brain injury on postnatal ultrasonography, severe retinopathy of prematurity, necrotizing enterocolitis, or late-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 23 publications
2
55
0
6
Order By: Relevance
“…The onset of breathing is a critical determinant of cardiovascular adaptation in newborns, and may be a key determinant of the size and effect of delayed cord clamping on patient outcomes (NBA, 2016). The Australian Placental Transfusion Study, a recently published RCT, randomised 1566 infants less than 30-week gestation to immediate cord clamping (within 10 s of delivery) compared with delayed cord clamping (60 s or more) (Tarnow-Mordi et al, 2017). The study found no significant difference in the study's primary composite outcome of death or major morbidity.…”
Section: What Do We Know: the Evidence Underpinning Pbm For Neonates mentioning
confidence: 99%
“…The onset of breathing is a critical determinant of cardiovascular adaptation in newborns, and may be a key determinant of the size and effect of delayed cord clamping on patient outcomes (NBA, 2016). The Australian Placental Transfusion Study, a recently published RCT, randomised 1566 infants less than 30-week gestation to immediate cord clamping (within 10 s of delivery) compared with delayed cord clamping (60 s or more) (Tarnow-Mordi et al, 2017). The study found no significant difference in the study's primary composite outcome of death or major morbidity.…”
Section: What Do We Know: the Evidence Underpinning Pbm For Neonates mentioning
confidence: 99%
“…The subsequent meta‐analysis of 27 clinical trials included 2834 preterm infants: the practice to postpone the cord clamping at ≥30 s after the birth was associated with decrease of in‐hospital mortality and need for transfusions, whereas the incidence of major neonatal morbidities was not affected . Finally, a recent randomized trial has compared early (≤10 s) and delayed (≥60 s) clamping in 1566 preterm neonates: although no differences in the primary outcome of death or major morbidities were reported, less infant in the delayed‐clamping group received subsequent RBC transfusion by 36 weeks of postmenstrual age .…”
Section: Anaemia In Term and Preterm Neonatesmentioning
confidence: 99%
“…In conclusion, autologous UCB can cover the perioperative transfusion supplies in full‐term neonates undergoing surgery . In contrast, in preterm neonates, the most appropriate strategy to reduce the need for allogeneic transfusion seems to be the delayed umbilical cord clamping [ ] .…”
Section: Review Of Studies On Umbilical Cord Blood As a Source For Trmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis 2 has provided the first high quality evidence that delayed cord clamping (DCC) reduces hospital mortality in pre‐term infants compared with immediate cord clamping (ICC). These findings were largely driven by the recently completed Australian Placental Transfusion Study (APTS), 3 which showed lower mortality in the DCC group than in the ICC group (6.4% v 9.0%), a difference that was not significant in post hoc adjustment for secondary outcomes ( P = 0.39). Further, there was an overall reduction in red cell transfusions in the DCC group compared with the ICC group (52.1% v 60.5%; P = 0.001), 3 which was also shown in the systematic review 2 .…”
mentioning
confidence: 99%
“…These findings were largely driven by the recently completed Australian Placental Transfusion Study (APTS), 3 which showed lower mortality in the DCC group than in the ICC group (6.4% v 9.0%), a difference that was not significant in post hoc adjustment for secondary outcomes ( P = 0.39). Further, there was an overall reduction in red cell transfusions in the DCC group compared with the ICC group (52.1% v 60.5%; P = 0.001), 3 which was also shown in the systematic review 2 . The only potential harm identified was an increased incidence of polycythemia, with an increased risk difference of 3%, although this was not associated with morbidity.…”
mentioning
confidence: 99%